Analisis Yuridis Peran Serta Pemerintah Indonesia Dalam Perdagangan Internasional - Ukas, Ukas; Arman, Zuhdi (Yayasan Tri Edukasi Ilmiah, 2024)
International Trade Law (HDI) in Indonesia has been formally established since the ratification of Law No. 7 of 1994 concerning Ratification and Participation of Indonesia as one of the participating countries in the GATT-WTO in Marrakech Geneva Morocco 1994. International Trade Law is part of the current knowledge of Legal Science. This development is very rapid considering that the business world in the movement of goods, services and investments (TRIMs) as well as IPR through customs requires a special legal umbrella apart from the relevant National Law, the Civil Code, the Commercial Code and several regulatory products. Other legislation. In International Trade strives for readers to understand, analyze and construct the basic things in international trade both nationally and internationally.